Clitoris to Urethral Meatus Distance, an Assumed Marker of Prenatal Androgen Exposure is not Correlated with the Obesity Compared to the Anogenital Distance - Zheng Li; Mengjiao Xu; Hong Xia; Huaifang Li; Binggen Zhu (IMR Press, 2022)
Background: The distance between clitoris and urethral meatus (CUMD) for women has been considered to likely reflect the extent of prenatal androgen exposure, being similar to the anogenital distance (AGD) and the digit length ratio. But no published work has examined the association between CUMD and AGD or digit ratio, and the effects of body weight on the CUMD and AGD. Methods: The CUMD and two AGD measurements, including the anus to the anterior clitoris (AGD-AC) and the anus to the posterior fourchette (AGD-AF), were taken in 117 Chinese women (18-45 years), using a digital caliper. The digit ratios were measured from photos by a digital camera. Meanwhile, data of their height, weight, and body mass index (BMI) were collected. Results: In bivariate correlation analyses of all 117 subjects, two AGD measurements (AGD-AC and AGD-AF) were moderately correlated with one another (r = 0.474, p < 0.001), but the correlation between AGD-AC and CUMD was weak (r = 0.172, p = 0.063). Both AGD-AC and AGD-AF were notably correlated with weight (r = 0.290, p = 0.002 and r = 0.189, p = 0.041; respectively) and BMI (r = 0.341, p < 0.001 and r = 0.204, p = 0.027; respectively), whereas the CUMD did not differ based on weight or BMI. Exclusion of obese individuals, the CUMD of 86 non-overweight subjects was correlated with the AGD-AC (r = 0.236, p = 0.028). Conclusions: These results indicated that the CUMD, as an assumed marker of prenatal androgen exposure, was not affected by the body weight, thus being superior to AGD-AC or AGD-AF.